2020
DOI: 10.1590/1519-6984.218391
|View full text |Cite
|
Sign up to set email alerts
|

Leaf application of chitosan and physiological evaluation of maize hybrids contrasting for drought tolerance under water restriction

Abstract: It is a fact that the regions that cultivate the most maize crop do not have fully adequate technologies to measure productivity losses caused by irregularities in water availability. The objective of this study was to evaluate the physiological characteristics of maize hybrids tolerant (DKB 390) and sensitive (BRS 1030) to drought, at V5 growth stage and under water restriction, in order to understand the mechanisms involved in the induction of tolerance to drought by chitosan in contrasting maize genotypes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…Maintaining the RWC and the photosynthetic pigments due to CSNPs in the current study may also explain its role as a plant growth enhancer. Enhancing the RWC in this study may be ascribed to the role of CSNPs in inducing the stomatal closure through the activation of ABA signaling pathway [40]. Increasing the RWC by CSNPs has been previously reported [41].…”
Section: Discussionsupporting
confidence: 61%
“…Maintaining the RWC and the photosynthetic pigments due to CSNPs in the current study may also explain its role as a plant growth enhancer. Enhancing the RWC in this study may be ascribed to the role of CSNPs in inducing the stomatal closure through the activation of ABA signaling pathway [40]. Increasing the RWC by CSNPs has been previously reported [41].…”
Section: Discussionsupporting
confidence: 61%
“…1). It could be concluded that the drought-induced limitation of photosynthesis in maize was primarily due to CO 2 diffusion e ciency from sub-stomatal interval internal cavities to carboxylation site in chloroplasts and degree of SC, and increasing evidences in maize also supported our results by Liu et al [5],Veroneze-Júnior et al [41], Perdomo et al [42], and He et al [4]. Therefore, genetic improvement of photosynthetic performances in maize can be applied to MAS breeding to improve drought tolerance and high-yielding in the future.…”
Section: Discussionsupporting
confidence: 89%
“…Chitosan application has the potential to mitigate the water deficit effects on yield and quality of wheat (Triticum aestivum L.) [23], and in the same plant species chitosan nanoparticles decrease the adverse effects of drought stress [24]. Similarly, leaf application of chitosan renders maize (Zea mays L.) hybrids more tolerant to water stress [25] and decreases the plant damage under drought stress in sesame (Sesamum indicum L.) [26]. Chitosan furnished as water solution alleviates water stress in marjoram (Origanum majorana L.) [27], and application of chitosan solution during sowing increases resistance against drought stress and the amount of oil in rape (Brassica napus L.) [28].…”
Section: Chitin-and Chitosan-based Derivatives In Plant Protection Agmentioning
confidence: 99%